2019
DOI: 10.1186/s12884-019-2460-y
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin levels in maternal serum and umbilical cord blood at birth by mode of delivery: relationship to anthropometric measurements and fetal sex

Abstract: Background The rate of cesarean section is increasing worldwide. Adiponectin is a hormone related to anti-inflammatory and anti-atherogenic effects; and it′s concentrations may change in response to inflammatory situations including surgical intervention. The aim of the current study was to investigate serum adiponectin levels in maternal and umbilical cord blood according to different modes of delivery and their relationship with anthropometric measurements and fetal sex. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…On the other hand, an increase in adiponectin in both MP and UCP in Enterotype II group was observed. Daryasari et al observed differences on maternal plasma adiponectin levels depending on the mode of delivery [43]. They found that umbilical cord blood from vaginal delivery had higher levels of adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an increase in adiponectin in both MP and UCP in Enterotype II group was observed. Daryasari et al observed differences on maternal plasma adiponectin levels depending on the mode of delivery [43]. They found that umbilical cord blood from vaginal delivery had higher levels of adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…However, investigating leptin in first and second trimester blood samples of 582 pregnant women did not identify any sex dependent difference [ 30 ]. Angiopoietin levels seem not different between women carrying a boy vs. women carrying a girl [ 102 ].…”
Section: Placental Hormones: Role In Glucose Metabolism and Sex Dimorphismmentioning
confidence: 99%
“…The exact mechanism of how maternal adiponectin levels can affect birthweight still deserves more investigation. While there are studies that did not find this association, 25,35 other authors observed a negative association. 36 However, our result corroborates with another recent study that showed a positive association between maternal adiponectin and birthweight.…”
Section: Discussionmentioning
confidence: 90%
“…21,22 Since adiponectin has an essential role in insulin metabolism and that glucose and insulin are crucial for fetal growth, maternal adiponectin may play an important role in fetal development; however, the literature results about this association are still controversial. [23][24][25] The aim of the present study was to evaluate serum adiponectin concentration in pregnant adolescents between 30 and 36 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%